Impact of conservation agriculture on maize yield and food security: Evidence from smallholder farmers in Zimbabwe - Siziba, Shephard; Nyikahadzoi, Kefasi; Makate, Clifton; Mango, Nelson (African Association of Agricultural Economists, 2019)
Conservation agriculture is promoted as a green technology that enhances the productivity and food security of farmers. However, there is limited evidence from practising farmers regarding these expected outcomes. This study evaluates the impact of conservation agriculture on the productivity of maize and food security outcomes among smallholder farmers in Zimbabwe. The propensity score-matching approach was used to estimate the impact. The data is based on a 2013 survey of 488 households. Conservation agriculture, largely defined by the use of planting basins, had a positive and significant (p < 0.05) impact on maize grain yield (ATT = 473 kgha-1), with the magnitude more pronounced among female-headed households (ATT = 515.53 kgha-1). The increased grain production extended the households’ grain self-provision period by 1.14 months for the pooled sample, and by a slightly longer period of 2.89 months for the female-headed sample. The study concludes that conservation agriculture increases maize productivity and grain supply to households, particularly for female-headed households.